Breaking up: Experimental insights into economic (dis)integration - Gabriele Camera; Lukas Hohl; Rolf Weder (University of Basel, Center of Business and Economics (WWZ), 2019)
Standard international economic theory suggests that people should embrace economic integration because it promises large gains. But recent events such as Brexit indicate a desire for economic disintegration. Here we report results of an experiment, based on a strategic analytical framework, of how size and distribution of potential gains from integration influence outcomes and individuals' inclination to embrace integration. We find that cross-country inequality in potential gains acts as a friction to realize those gains. This suggests that to better understand recent phenomena, international economic theory should account for distributional considerations and behavioral aspects it currently ignores.
Keywords: C70; C90; F02; 330; endogenous institutions; globalization; indefinitely repeated games; social dilemmas